Effects of information technology failures on the market value of firms - Bharadwaj, Anandhi; Keil, Mark; Mähring, Magnus (The journal of strategic information systems, 2009)
IT failures abound but little is known about the financial impact that these failures have on a firm’s market value. Using the resource-based view of the firm and event study methodology, this study analyzes how firms are penalized by the market when they experience unforeseen operating or implementation-related IT failures. Our sample consists of 213 newspaper reports of IT failures by publicly traded firms, which occurred during a 10-year period. The findings show that IT failures result in a 2% average cumulative abnormal drop in stock prices over a 2-day event window. The results also reveal that the market responds more negatively to implementation failures affecting new systems than to operating failures involving current systems. Further, the study demonstrates that more severe IT failures result in a greater decline in firm value and that firms with a history of IT failures suffer a greater negative impact. The implications of these findings for research and practice are discussed.